Bit wise and delay of vedic multiplier - Kumar, M Siva; Kumar Tulasi, Sanath; Srinivasulu, N; Lakshmi Bandi, Vijaya; Hari Kishore, K (International Journal of Engineering and Technology, 2017)
The Vedic multiplier is derived from the ancient mathematics called Vedic mathematics .The ancient mathematics has different sutras in that we use Urdhva Tiryagbhyam sutra which means clock wise and vertically . As we know that binary multiplication is not possible so that instead we use binary addition or subtraction instead of it. The key process for the multiplication is the speed of the processor. The fastest mode of multiplication is the Vedic multiplier. In this paper we want to show the delay and utilization of components available for the multiplier by executing the code. The comparison of delay from some papers was also proposed in this paper. The research is going on the Vedic mathematics to overcome the problems on the conventional mathematics. In future Vedic multiplier plays an important role in the DSP (Digital Signal Processing).As it is the fastest and efficient mode of operation. In this paper I am calculating the bit wise delay up to 32-bit. The whole analysis was done in Xilinx. The ISM wave forms for every bit up to 32-bit was to be obtained. The utilization, used, available, utilized analysis was also taken. The whole process was done in XILINX software.